Nature of Research Proposals Submitted to Institute of Medicine Institutional Review Committee: A Retrospective Review - Tiwari, Ashish; Sharma, Mohan Raj; Shrestha, Lava; Bali, Kanchana; Bhatta, Om Prakash (Journal of Nepal Health Research Council, 2025)
Background : Efficient evaluation of research proposals is crucial for ensuring ethical standards and scientific rigor in healthcare. This study aims to analyze the proposals submitted to the Institutional Review Committee (IRC) of the Institute of Medicine (IOM) to determine the trends in health-related research conducted in a major institute. Methods: This is a retrospective review of research proposals submitted to the IRC of IOM from May 2019 to April 2021. The analysis focused on the institutional/departmental affiliation of investigators, gender of the principal investigator (PI), funding sources, ethical issues, types of proposals, and research design. Results: Out of 769 proposals submitted, seven were rejected (acceptance rate of 99.1%). There was a steady increase in the number of submissions over the study period. Descriptive cross-sectional studies were the most frequent 630 (82.6%) followed by randomized controlled trials. More than half [403, 52.9%] proposals were related to health promotion. The clinical departments contributed 443 (58.1%) submissions. Males outnumbered females (54.2% vs 45.8%) and only 53 (7.0%) were funded. Conclusions: Cross-sectional studies with a focus on health promotion were the most common submissions for ethical approval at the IOM. Policymakers in our institute and other institutions can use this research to set priorities for promoting research. Keywords: Ethical review, Institutional Review Board, Researchers, research proposal